2010
DOI: 10.4269/ajtmh.2010.09-0355
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Spotted Fever Group and Typhus Group Rickettsial Infection in the Amazon Basin of Peru

Abstract: Abstract. A seroprevalence study for IgG antibodies against spotted fever group (SFGR) and typhus group (TGR) Rickettsia among humans and domestic pets was conducted in the city of Iquitos, located in the Amazon basin of Peru. Of 1,195 human sera analyzed, 521 (43.6%) and 123 (10.3%) were positive for SFGR and TGR antibodies, respectively. District of residence and participant age were associated with antibody positivity for both groups, whereas rodent sightings in the home were associated with TGR antibody po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
7
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 38 publications
5
29
7
3
Order By: Relevance
“…Evidence of the spotted fever group (SFG) rickettsial infections have been documented from diverse areas of Peru (Schoeler et al 2005, Forshey et al 2010, including a 2002 outbreak in Sapillica, Piura, Peru. Serological evidence from villagers during that outbreak showed that the prevalence of immunoglobulin M (IgM) antibody to SFG rickettsiae ranged from 10% to 19% among the human population (Blair et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the spotted fever group (SFG) rickettsial infections have been documented from diverse areas of Peru (Schoeler et al 2005, Forshey et al 2010, including a 2002 outbreak in Sapillica, Piura, Peru. Serological evidence from villagers during that outbreak showed that the prevalence of immunoglobulin M (IgM) antibody to SFG rickettsiae ranged from 10% to 19% among the human population (Blair et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, higher seroprevalence values have been reported from other countries. A seroprevalence of 10.3% for the typhus group was reported from the Peruvian Amazon Basin (Forshey et al 2010). A study in Spain showed a seroprevalence against R. typhi and R. felis of 3.8-18% and 3.2-6.5%, respectively (Bernabeu-Wittel et al 2006, Nogueras et al 2006, Bolañ os-Rivero et al 2011.…”
mentioning
confidence: 96%
“…17 In addition, the 17kD sequences obtained in this study were identical with Rickettsia sp. RF2125, which was detected in fleas obtained from the United States, 18 Peru, 19 and Uruguay. 20 Although existing data suggest a worldwide distribution of Rickettsia sp.…”
mentioning
confidence: 99%